2022
DOI: 10.1136/jitc-2022-005018
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibodies targeting CD40 and tumor-associated antigens promote cross-priming of T cells resulting in an antitumor response superior to monospecific antibodies

Abstract: BackgroundIndications with poor T-cell infiltration or deficiencies in T-cell priming and associated unresponsiveness to established immunotherapies represent an unmet medical need in oncology. CD40-targeting therapies designed to enhance antigen presentation, generate new tumor-specific T cells, and activate tumor-infiltrating myeloid cells to remodel the tumor microenvironment, represent a promising opportunity to meet this need. In this study, we present the first in vivo data supporting a role for tumor-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…The functionality of RUBY bsAbs was evaluated in a variety of assays. It was shown that a CD40-EpCAM RUBY bsAb displayed conditional CD40 activation in a reporter assay, similar to what has been shown by Hägerbrand et al 29 The bsAb induced activation of CD40-expressing cells only in the presence of EpCAM expressed on CHO cells whereas no activation was observed in a similar set up with CHO cells lacking EpCAM expression ( Figure 3(b) ). Additionally, a CD137-5T4 RUBY bsAb induced potent T cell activation as measured by a dose-dependent increase in interferon (IFN)-gamma release in the presence of 5T4.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The functionality of RUBY bsAbs was evaluated in a variety of assays. It was shown that a CD40-EpCAM RUBY bsAb displayed conditional CD40 activation in a reporter assay, similar to what has been shown by Hägerbrand et al 29 The bsAb induced activation of CD40-expressing cells only in the presence of EpCAM expressed on CHO cells whereas no activation was observed in a similar set up with CHO cells lacking EpCAM expression ( Figure 3(b) ). Additionally, a CD137-5T4 RUBY bsAb induced potent T cell activation as measured by a dose-dependent increase in interferon (IFN)-gamma release in the presence of 5T4.…”
Section: Resultssupporting
confidence: 83%
“…These results are in line with efficient tumor localization of a RUBY bsAb previously seen in vivo in tumor-bearing mice. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported the immunostimulators mainly focus on the tumor necrosis factor receptor (TNFR) family and B7-CD28 family. Currently, a number of agonistic antibodies have entered the clinical stage (44)(45)(46). TNFRSF4, also known as OX40, activates the PI3K/PKB, NF-kB1 and NFAT pathways and enhances T cell-mediated antitumor immunity, thereby improving survival in several preclinical cancer models, including B16 melanoma and lung cancer (47).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it cannot be concluded whether antigen fate or DC maturation induced by CD40 targeting was the main determinant for the enhanced T cell proliferation. Of note, an exciting prospect in the context of CD40 targeting are bispecific antibodies recognizing CD40 and a TAA. , These constructs bring tumor debris in proximity to CD40 + cells, which can take up, process, and present the tumor antigens, while simultaneously being stimulated via CD40. This results in antitumor responses surpassing immune reactivity toward the initial targeted epitope …”
Section: Promoting Pan-apc Antigen Presentationmentioning
confidence: 99%